Challenges and Opportunities in the Management of Guidance Services in Elementary Schools: The Roles of Teachers, Counselors, and School Principals - Sonia Yulia Friska; Laila Fadilla Eka Putri Efendi; Sekarhayu Kanaya (Institution of Scientific Publishing and Publication of the Yayasan Dzaky Elmumtaz Qurani, 2025)
This study aims to examine guidance management in elementary schools through the roles of teachers, counselors, and principals in supporting students’ academic, social, and emotional development. The method employed was a literature review by analyzing various scientific sources, including books, journal articles, and research reports relevant to guidance and counseling in elementary education. The collected data were categorized based on the roles of each educational actor and then analyzed using a qualitative descriptive approach. The findings indicate that teachers act as initial facilitators who provide guidance and emotional support to students, school counselors function as professional personnel who systematically address students’ personal and social issues, while principals serve as leaders who coordinate and support the sustainability of guidance programs. The results also emphasize that effective collaboration among teachers, counselors, and principals is a key factor in the success of guidance management in elementary schools. Well-planned and integrated guidance management has been shown to contribute to increased learning motivation, psychological well-being, and students’ character development. Therefore, strengthening synergy and leadership in guidance services should be a primary concern in efforts to achieve holistic elementary education.